The Requirement for Hydrostatic Initialisation in LS-DYNA/USA Finite Element Models - Lloyd Hammond; Raphael Grzebieta (Shock and Vibration)
The LS-DYNA/USA (Underwater Shock Analysis) coupled finite element codes are being investigated as a tool for predicting the local response of compliant plate structures subjected to far-field underwater explosion.